Comparative study on quality of whole milk processed by high hydrostatic pressure or thermal pasteurization treatment. (June 2020) - Liu, Guanchen; Carøe, Christina; Qin, Zihan; Munk, Daniel M.E.; Crafack, Michael; Petersen, Mikael A.; Ahrné, Lilia
Abstract: Quality of whole milk pasteurized by high hydrostatic pressure processing (HPP: 600 MPa for 5 min) or HPP combined with microfiltration (MF + HPP) were compared with two conventional heat treatments, low temperature long time (LTLT: 63 °C for 30 min) and high temperature short time (HTST: 72 °C for 15 s). Inactivation of microorganisms, changes in volatiles, protein denaturation, gastric digestion, and sensory quality were evaluated after 8 days of storage at 5 °C. Total bacterial and E.coli counts were reduced to approximately the same level for both high pressure and heat treated milks. The denaturation of β-lactoglobulin was significantly higher for high-pressurized milks, while no significant differences were found in gastric in-vitro protein digestion compared with heat treated milks. The results of volatile compounds revealed that HTST and HPP-treated milks exhibited very similar aroma profiles, while LTLT-milks were characterized by higher levels of ketones. After 8 days storage, the sensory analysis showed that LTLT milk was the one that differed most from the other three milks with highest intensities of all the sensory attributes, while no tangible differences were found between HTST and any HPP and MF + HPP milk, except for Boiled Taste that was slightly but significantly lower for MF + HPP. Highlights: Quality attributes of HPP treated milk compared with HTST were not tangible. HPP causes higher denaturation of β-Lg than HTST but similar in-vitro digestion. All treatments impaired the volatile profile in comparison with raw milk. Volatile profile of HPP and HTST treated milks were similar but differ from LTLT. HPP + MF has lower boiled taste than HTST by sensorial evaluation.